Diversity of Penaeidae at the Mengkudu Bay Waters, North Sumatra, Indonesia - EDI AZWAR; SULARNO SULARNO; FRANSISKUS PERIODE WARUWU; MHD. RAFI’I MA’ARIF TARIGAN; SYARIFAH WIDYA ULFA; AULIA JUANDA DJAINGSASTRO (Society for Indonesian Biodiversity, 2023)
Abstract. Azwar E, Sularno, Waruwu FP, Tarigan MRM, Ulfa SW, Djaingsastro AJ. 2023. Diversity of Penaeidae at the Teluk Mengkudu Waters, North Sumatra, Indonesia. Biodiversitas 24: 1376-1384. Microscopic animals play an important role in the growth of marine biota. Crustaceans are a marine biota group often found in waters and have high economic value. Crustaceans also have a significant role in coral reef ecosystems, contributing around 20% of all invertebrate species. Crustaceans are an important group of microbenthic fauna in coastal ecosystems, ranging from mangroves, coral reefs, and seagrass ecosystems. This present study was conducted from April to June 2022 to identify Penaeidae diversity in Teluk Mengkudu waters, Serdang Bedagai District, North Sumatra Province, Indonesia. Furthermore, it used a purposive sampling method to harvest crustacean species near the waters. An exploratory method was applied with quantitative data collection to select Penaeidae crustaceans from the catches retrieved by fishermen. The tools used in this study were boat, net, fiber, knife, compass, flags, camera, notebook, ice cubes, a thermometer, pH meter, and DO meter. The material used in this study was shrimp caught by fishers. Data collection techniques used interviews and documentation with fishing communities about catching crustaceans at the study site. Data analysis uses the formula diversity, evenness, knowledge richness, and dominance index. Based on the results, Penaeus indicus H.Milne Edwards, 1837 and Metapenaeus ensis (De Haan, 1844) were the two species obtained from the Penaeidae family. The evenness index for P. indicus and M. ensis was respectively highest in June (0.237 and 0.519) but lowest in May (0.203 and 0.510) with a total value of 2.212. Also, the prominent richness index for both species was respectively highest in June (5.762 and 29.371) but lowest in May (4.568 and 27.053). The highest dominance index (D) was measured in May, where the highest D value of P. indicus was 0.003, and the lowest was 0.002. The highest D of M. ensis was discovered in June, namely 0.086, while the lowest, at 0.073, was recorded in May, and in general, both species had a total D of 0.245. Parameters of salinity, pH, temperature, substrate, and oxygen strongly influence crustacean diversity. The parameters measured in the study area included temperature (28?), salinity (20-35 ppt), DO (6.8 mg/L), and pH (6.7).